Atmospheric circulation of brown dwarfs and directly imaged exoplanets driven by cloud radiative feedback: effects of rotation - Tan, X; Showman, AP (Oxford University Press, 2021)
Observations of brown dwarfs (BDs), free-floating planetary-mass objects, and directly imaged extrasolar giant planets (EGPs) exhibit rich evidence of large-scale weather. Cloud radiative feedback has been proposed as a potential mechanism driving the vigorous atmospheric circulation on BDs and directly imaged EGPs, and yet it has not been demonstrated in three-dimensional dynamical models at relevant conditions. Here, we present a series of atmospheric circulation models that self-consistently couple dynamics with idealized cloud formation and its radiative effects. We demonstrate that vigorous atmospheric circulation can be triggered and self-maintained by cloud radiative feedback. Typical isobaric temperature variation could reach over 100 K and horizontally averaged wind speed could be several hundreds of $\, {\rm m\, s^{-1}}$. The circulation is dominated by cloud-forming and clear-sky vortices that evolve over time-scales from several to tens of hours. The typical horizontal length-scale of dominant vortices is closed to the Rossby deformation radius, showing a linear dependence on the inverse of rotation rate. Stronger rotation tends to weaken vertical transport of vapour and clouds, leading to overall thinner clouds. Domain-mean outgoing radiative flux exhibits variability over time-scales of tens of hours due to the statistical evolution of storms. Different bottom boundary conditions in the models could lead to qualitatively different circulation near the observable layer. The circulation driven by cloud radiative feedback represents a robust mechanism generating significant surface inhomogeneity as well as irregular flux time variability. Our results have important implications for near-infrared (IR) colours of dusty BDs and EGPs, including the scatter in the near-IR colour–magnitude diagram and the viewing-geometry-dependent near-IR colours.